2019
DOI: 10.7717/peerj.8223
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation dynamic analysis based on multisource remote sensing data in the east margin of the Qinghai-Tibet Plateau, China

Abstract: This study focuses on the vegetation dynamic caused by global environmental change in the eastern margin of the Qinghai-Tibet Plateau (EMQTP). The Qinghai–Tibet Plateau (QTP) is one of the most sensitive areas responding to global environmental change, particularly global climate change, and has been recognized as a hotspot for coupled studies on changes in global terrestrial ecosystems and global climates. An important component of terrestrial ecosystems, vegetation dynamic has become a key issue in global en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
(65 reference statements)
0
9
1
Order By: Relevance
“…Land-use change may also be an important explanation for the greening trend in some regions [30][31][32]. Unlike the present study, a clear inflection point of the greening trend was also found in the eastern part of the Tibetan Plateau, which may be due to the different vegetation types and altitudes [33]. Seasonally, both datasets showed a comparable number of growing cycles in most regions but with diverse amplitudes.…”
Section: Discussioncontrasting
confidence: 75%
“…Land-use change may also be an important explanation for the greening trend in some regions [30][31][32]. Unlike the present study, a clear inflection point of the greening trend was also found in the eastern part of the Tibetan Plateau, which may be due to the different vegetation types and altitudes [33]. Seasonally, both datasets showed a comparable number of growing cycles in most regions but with diverse amplitudes.…”
Section: Discussioncontrasting
confidence: 75%
“…Comparing with Figure 1, it could be seen that the forest land de-creased by 6.53% and 6.37% from 2009 to 2018 KDZs around Zhengzhou and APZs around Jinan and Zhengzhou, respectively. Interestingly, forest land area had significantly decreased in KEFZs around Lhasa which was always ecologically fragile [31]. This was due to the fact that the total area of the forest land was small, and a few changes would cause the overall ratio to change.…”
Section: Changing Of Ecological Land Typesmentioning
confidence: 99%
“…Based on Systeme Probatoire d'Observation de la Terre (SPOT)/normalized difference vegetation index (NDVI) data, Ding et al [12] found that the spatial and temporal distribution of alpine grassland phenology from 1999 to 2009 was closely related to hydrothermal conditions, and the SOS was delayed with the gradual deterioration of hydrothermal conditions. Wang et al [13] used Global Inventory Modeling and Mapping Studies (GIMMS)/NDVI and SPOT/NDVI data to analyze vegetation phenology trends on the eastern edge of the Tibetan Plateau and found that the SOS in the region showed an early trend from 1982 to 1998, while a delayed trend was observed from 1999 to 2018. In a small-scale regional study, An et al [14], based on Landsat 7 ETM+ (Enhanced Thematic Mapper Plus) and Landsat 8 OLI (Operational Land Imager) data from 2013 to 2015 along a 2600 km transect in the center of the Tibetan Plateau, investigated how vegetation changes in response to differences in slope aspect and elevation.…”
Section: Introductionmentioning
confidence: 99%